1991
DOI: 10.1063/1.349280
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport in thin films of copper silicide

Abstract: Electrical properties of thin films of η′-Cu3Si phase with a tetragonal crystal structure are reported on. Electrical transport in these films is found to be very sensitive to oxygen exposure. Cu3Si reacts with oxygen at room temperature to form both Si and Cu oxides, resulting in high-room-temperature (∼60 μΩ cm) and even nonmetallic resistivity. This behavior is contrasted with that of low-resistivity (∼5 μΩ cm at room temperature) Cu3Ge, which is inert in an oxygen environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 8 publications
4
28
0
Order By: Relevance
“…On the other hand, the room-temperature resistivity shown in Fig. 3 for a specimen with a 45 nm grain size is 8.8 mU cm, which is comparable to the range of 6e10 mU cm reported for 0.2 mm thin films of Cu 3 Ge having grain sizes in the range of 0.1e 1 mm [25,26,38]. Again, this indicates that grain boundaries are not a significant contributor to the overall resistivity.…”
Section: Electrical Propertiessupporting
confidence: 75%
See 1 more Smart Citation
“…On the other hand, the room-temperature resistivity shown in Fig. 3 for a specimen with a 45 nm grain size is 8.8 mU cm, which is comparable to the range of 6e10 mU cm reported for 0.2 mm thin films of Cu 3 Ge having grain sizes in the range of 0.1e 1 mm [25,26,38]. Again, this indicates that grain boundaries are not a significant contributor to the overall resistivity.…”
Section: Electrical Propertiessupporting
confidence: 75%
“…In contrast to Cu, the 3 1 compound Cu 3 Ge has been reported to be resistant to oxidation to temperatures in excess of 400 C and has better adhesion characteristics while suppressing the diffusion of Cu into silicon [23,24]. It has also been reported that Cu 3 Ge has a room-temperature resistivity of 6e10 mU cm which is nearly a constant value over a wide composition range from 25 at% to 35 at% Ge [25,26]. This compound was shown to have a reduced resistivity comparable to high purity copper when small amounts of Ga or Au are added.…”
Section: Introductionmentioning
confidence: 94%
“…The thin film studies of Aboelfotoh et al, demonstrated that the presence of eta phase Cu 3 Si catalyzed the oxidation of silicon to form a film of silicon and copper oxides which exhibited a nonmetallic resistivity ͑60 ⍀ cm͒. 10 In another study, the Schottky-barrier behavior of Cu 3 Si in n-type and p-type silicon has been investigated. 11 Because these bulk phase studies measure properties which are averages of local systems, specific information about the interactions between the individual metal and silicon atoms is not obtained.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to preferential oxidation of silicon during the initial stage of reactive sputtering of the copper alloy target. 13 Fig. 2c.…”
Section: Resultsmentioning
confidence: 97%